(3QSGdI aj BOGH GdefGXQIs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje jbhd GdabjQ Edi QH GdYHGO GdbOjQ deG cGf eJhf Yde GdBOGH de JTJed Ydi JaUjd CeKdI GdHMK dLejY GdCHhGH LYdJ gPg GdQSGdI GdeTJedI Ydi PG gOjI TGajI dUOhQ GdENhGf s
(3BNQgG (B:s
(3eKGd gPg GdCHMGK Cf Jbhd gPG GdJUfja jLH JUOjQg HGdMeO hdG JTJZd HGdESJOdGd YdjgG ajJhLg Ydjc efY gPg GdOYhi Ch fbVgG Ch eYGQVJgG hEf ETJYdJ HGdOdjd YdjgG JeJ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs